Characteristics and management of congenital anophthalmos and microphthalmos at a tertiary eye hospital - Galindo-Ferreiro, Alicia; Elkhamary, Sahar M; Alhammad, Fatimah; AlGhafri, Laila; AlWehaib, Manar; Alessa, Dalal; Aldossari, Saif; Akaishi, Patricia; Khadekar, Rajiv; AlShaikh, Osama; Schellini, Silvana Artioli [UNESP] (Taylor & Francis, 2019)
Purpose: The purpose of the study is to evaluate demographic data and outcomes of the management of congenital anophthalmia/microphthalmia. Methods: This retrospective, descriptive, cross-sectional study evaluated patients with congenital anophthalmia/microphthalmia managed from 2004 to 2014 at a tertiary hospital in Saudi Arabia. Data were collected on patient age, gender, cause, orbital status, laterality, systemic comorbidities, ocular evaluation, and management (type of surgery, type of orbital implant, and complications). The main outcome measure was the ability to hold the prosthesis. Results: The study sample was composed of 513 eyes/sockets of 365 patients. Two-hundred and seventeen (59.4%) patients were unilateral cases. Forty-one (8%) sockets were due to congenital anophthalmia and 471 (92%) were due to microphthalmia. There were 73.2% isolated cases and 28.5% with systemic involvement. Systemic involvement was more common in bilateral cases. The most commonly associated conditions were central nervous disorders. One-hundred and nineteen (46.7%) cases had parental consanguinity. Two hundred and eighteen eyes/sockets (163 patients) underwent surgery including conjunctival flap (38; 17.4%), evisceration (38; 17.4%), enucleation (16; 7.3%), or procedures to improve the anophthalmic socket volume (45; 20.6%). Volume enhancing procedures included polymethylmethacrylate orbital implants (26; 57.8%), expanders (11; 24.4%), integrated hydroxyapatite or polyethylene implants (2; 4.4%), and dermis-fat graft (6; 13.3%). In most cases, clinical or surgical management resulted in a successful outcome. Conclusion: Anophthalmia/Microphthalmia was detected in 36.5 patients/year. The majority had isolated microphthalmia. Good outcomes were achieved with clinical or surgical management in the majority of cases.
Keywords: Anophthalmia; congenital; disorders; microphthalmia; outcome